Kesesuaian antara pilihan cita-cita karir siswa sekolah menengah pertama dengan karir orang tua - Tanjung, Fauzzar Rahmi; Afdal, Afdal (Counseling and Humanities Review, 2023)
This research is motivated by phenomena related to the suitability and incompatibility between the choice of career aspirations of junior high school students and the careers of their parents. Career selection is influenced by several aspects including genetic influences, childhood experiences and individual needs. This study aims to describe the suitability between the career aspirations of junior high school students and their parents' careers. The research method is quantitative with descriptive research type. The research population was 55 people, a sample of 48 students, using a purposive sampling technique. Collecting data using a career choice questionnaire with a Likert scale model. The results of this study found: choice of career goals on the aspect of genetic influence in the high category (54.2%), choice of career aspirations on the aspect of childhood experience in the medium category (47.9%), choice of career aspirations in aspects of individual needs in the high category (60.4%). It was concluded that the choice of students' career aspirations is in accordance with the career of their parents, then counseling services are needed as a follow-up to determine the suitability of the choice of career aspirations with their talents and potential.